Concurrent validity and test-retest reliability of VALD ForceDecks strength, balance, and movement assessment tests - Collings, T. J.; Lima, Y. L.; Dutaillis, B.; Bourne, M. N. (Journal of Science and Medicine in Sport, 2024)
Objective To evaluate the concurrent validity and test-retest reliability of common movement, strength, and balance tests using portable uniaxial dual force plates.